Productivity costs due to human papillomavirus-related cancer mortality in the United Kingdom - Engelbrecht, Kayla; Ovcinnikova, Olga; Ntais, Dionysios; Shoel, Hayley; Meiwald, Anne; Hughes, Robert; Weston, Georgie; Morais, Edith; Bencina, Goran (Journal of medical economics, 2024)
Human papillomavirus (HPV) causes several cancers such as cervical cancer and some head and neck (oral cavity, pharynx, and larynx), vulval, vaginal, anal, and penile cancers. As HPV vaccination is available, there is potential to prevent these cancers attributed to HPV and consequently the burden associated with them. The aim of this analysis was to estimate the number of HPV-related cancer deaths and the productivity costs due to years of life lost (YLL) in the United Kingdom (UK). A model was developed utilizing UK 2019 mortality data sourced from country-specific databases for England, Scotland, Wales, and Northern Ireland for the following HPV-related cancers: head and neck (ICD-10 C00-14 and C32), cervix uteri (C53), vaginal (C51), vulval (C52), anal (C21), and penile (C60). The proportion of deaths and years of life lost (YLL) due to HPV were estimated using HPV attributable fractions for each anatomic locations from the published literature. Labor force participation, retirement ages, and mean annual earnings, discounted at 3.5% annually, were applied to YLL to calculate the present value of future lost productivity (PVFLP). A total of 1,817 deaths due to HPV-related cancers were reported in the UK in 2019 resulting in 31,804 YLL. Restricting to only YLL that occurred prior to retirement age yielded a total YPLL of 11,765 and a total PVFLP of £187,764,978. There is a high disease burden in the UK for HPV-related cancers, with a large economic impact on the wider economy due to productivity losses. Implementing and reinforcing public health measures to maintain high HPV vaccination coverage in both males and females may further facilitate reduction of this burden.